A novel C8orf37 splice mutation and genotype-phenotype correlation for cone-rod dystrophy. (2nd July 2016) - Rahner, Nils; Nuernberg, Gudrun; Finis, David; Nuernberg, Peter; Royer-Pokora, Brigitte
ABSTRACT: Background : To identify the disease-causing mutation in a consanguineous family of Morrocan origin with syndromic autosomal recessive (ar) cone-rod dystrophy (CRD) in two patients and describe genotype-phenotype correlations. Materials and Methods : Genome-wide homozygosity mapping and direct sequencing of C8orf37, located in a homozygous interval, was performed in the family. mRNA analysis revealed the effect of the newly identified splice-site mutation. For a comparative analysis phenotypic and genetic data of C8orf37 mutations were extracted from published cases. Results : The new splice-site mutation c.155+2T>C identified in the family results in a skipping of 82 bp. The CRD phenotypes of our patients were consistent with previous reports. Non-ocular findings in our patients and two previously described patients were postaxial polydactyly present at birth. Both families with additional postaxial polydactyly had splice site mutations affecting intron 1 of C8orf37, one at the slice donor and one at the splice acceptor site. Conclusions : This report extends the genotypic spectrum of C8orf37 -associated retinal dystrophies and demonstrates for the first time a genotype-phenotype correlation between an arCRD-polydactyly-association and truncating germline mutations affecting the N-terminal region of the protein. Furthermore, our findings underline the ciliary function of C8orf37 protein.